BUSINESS PROFIT AND THE PRICE LEVEL. - Bowers, Russell (The Accounting Review, 1951)
Abstract In a private enterprise economy with profit as the primary rational motive for production the correct reporting of profit is as important as a free market economy itself. The difference between nominal wages and real wages and nominal income and real income is an adjustment for change in price level measured by some general index. But similar distinction between nominal and real profits has not been widely accepted. This article illustrates quantitatively a distinction between real and nominal profit and shows some of its economic implications. In accounting for business income persistent use of the legal dollar at all times to measure cost and revenue has led to many unfortunate comparisons. The amount of money paid is usually considered to constitute cost as well as to measure cost. Real cost is, the value of economic resources over which money paid gives command. It is the general purchasing power of money paid which constitutes economic real cost and not the legal money itself. With a change in purchasing power of the dollar historical real costs become distorted unless corrected by an index of change in the general purchasing power of the dollar.